Antioxidant and Cytoprotective Effects of Different Compounds on Cyclophosphamide-induced Nephrotoxicity - Machado, Dayane Almeida; de Castro Oliveira, Natasha Moreira; Ceron, Carla Speroni; do Vale, Gabriel Tavares (Current Drug Research Reviews, 2025)
Cyclophosphamide is a drug derived from nitrogenous mustards and is mainly indicated for the anti-neoplastic clinic. When it is metabolized in the liver, it produces acrolein, a cytotoxic metabolite capable of generating damage to the body. The oxidative, nitrative and nitrosative stress are responsible for mediating this side effect since the toxicity of the drug induces the production of reactive species of oxygen (ROS) and nitrogen (RNS). These radicals are unstable and react with other molecules that can result in cellular lesions such as lipid peroxidation, enzymatic inactivation, and excessive activation of pro-inflammatory genes, producing molecules such as malonaldehyde (MDA) and nitric oxide (NO), representing oxidative stress markers. One of the consequences of these mechanisms is nephrotoxicity. In contrast, some compounds have direct or indirect antioxidante action, which are the objects of this study: gallic acid, aminoguanidine, chrysin, hesperidine, naringin, morin-5'-sulfonic acid sodium salt and spirulina. All of them are responsible for the nephroprotective activity when administered during experiments in vitro or in vivo. Thus, this observational bibliographic research is characterized as qualitative descriptive and explanatory, since it focuses on analyzing the antioxidant properties of compounds with possible potentials to inhibit the nephrotoxicity induced by cyclophosphamide and describe the results, in addition to clarifying the biochemical activities involved in the process.
Keywords: reactive species of oxygen